Kecemasan Neurosis Tokoh Eleanor dalam novel Eleanor Oliphant is Completely Fine karya Gail Honeyman - Ambiya, Alif Andaru (PT. Alahyan Publisher Sukabumi, 2024)
Neurotic anxiety is a form of anxiety originating from the Id or instinct, arising when desires remain unfulfilled, manifested as a sense of fear. Neurotic anxiety is rooted in the fulfillment of basic needs such as a sense of security. Individuals experiencing neurotic anxiety tend to worry about things that are unreal or exist only in their subconscious. This study examines the portrayal of neurotic anxiety in the character of Eleanor in Gail Honeyman's novel, Eleanor Oliphant is Completely Fine. A qualitative descriptive method with a literary psychology approach was employed. Data was collected through reading and note-taking. The findings revealed several manifestations of neurotic anxiety in Eleanor, including anxiety related to the trauma she has experienced.